2010
DOI: 10.1002/adma.201003601
|View full text |Cite
|
Sign up to set email alerts
|

Woven Electrochemical Transistors on Silk Fibers

Abstract: Fiber-based opto-electronic components such as light-emitting diodes (LEDs), [ 1 , 2 ] solar cells, [3][4][5] electrochromic pixels [ 6 ] and transistors [7][8][9][10][11][12] attract increasing attention for their alternative, nonplanar device architectures, which readily permit integration into 'smart' fabrics. Furthermore, devices such as transistors facilitate advanced patterning schemes of electronic circuitry through judicious weaving. [9][10][11][12] In particular conjugated polymers are suited as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 36 publications
0
127
1
2
Order By: Relevance
“…231 Coating of silk fibers 50-100 µm in diameter, has also been shown to be useful for fabrication of electrochemical transistors. 232 Addition of PEDOT-S during the growth step of collagen fibrils allowed for self-assembly of PEDOT-S coated collagen fibril, which could be imaged without conductive metal coatings in the electron microscope, Figure 30.…”
Section: Conductivity In Collagen Scaffoldsmentioning
confidence: 99%
“…231 Coating of silk fibers 50-100 µm in diameter, has also been shown to be useful for fabrication of electrochemical transistors. 232 Addition of PEDOT-S during the growth step of collagen fibrils allowed for self-assembly of PEDOT-S coated collagen fibril, which could be imaged without conductive metal coatings in the electron microscope, Figure 30.…”
Section: Conductivity In Collagen Scaffoldsmentioning
confidence: 99%
“…In the same way, manufacturing technology of a printed circuit board cannot provide meterscale pressure or touch sensors because the sizes are limited to several tens of centimeters and a large-area board is expensive. (14) Scalable fabrication technology for floor touch sensors (i.e., e-textile), (15)(16)(17) which is based on textile technology, has recently attracted much attention because automatic looming machines are considered a highly mature technology in use since the industrial revolution, which can produce several meter-wide fabrics continuously at a low cost. (15)(16)(17)(18)(19)(20)(21)(22) However, with the present technology, the sensor fibers have been woven manually, and there are few examples of automatic weaving of sensor fibers because the touch sensor fibers are sensitive to the destructive tension and friction produced by automatic looming machines.…”
Section: Introductionmentioning
confidence: 99%
“…(14) Scalable fabrication technology for floor touch sensors (i.e., e-textile), (15)(16)(17) which is based on textile technology, has recently attracted much attention because automatic looming machines are considered a highly mature technology in use since the industrial revolution, which can produce several meter-wide fabrics continuously at a low cost. (15)(16)(17)(18)(19)(20)(21)(22) However, with the present technology, the sensor fibers have been woven manually, and there are few examples of automatic weaving of sensor fibers because the touch sensor fibers are sensitive to the destructive tension and friction produced by automatic looming machines. (18)(19)(20)(21)(22) In fact, wrong tension is applied especially in the case of warp sensor fibers, resulting in threads being cut when the wefts are interlaced since the sensor fibers have a larger diameter than those of other conventional polyester or other fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Solution-processed nanoparticles with low viscosity are amenable to being printed into devices through low-cost and high-throughput inkjet or roll-to-roll printing techniques [78,81]. Jagannathan et al [223] demonstrated that organic nanoparticles are suitable for low-cost printing procedures.…”
Section: Introductionmentioning
confidence: 99%